2009
DOI: 10.1073/pnas.0907205106
|View full text |Cite
|
Sign up to set email alerts
|

MAP kinases MPK9 and MPK12 are preferentially expressed in guard cells and positively regulate ROS-mediated ABA signaling

Abstract: Reactive oxygen species (ROS) mediate abscisic acid (ABA) signaling in guard cells. To dissect guard cell ABA-ROS signaling genetically, a cell type-specific functional genomics approach was used to identify 2 MAPK genes, MPK9 and MPK12, which are preferentially and highly expressed in guard cells. To provide genetic evidence for their function, Arabidopsis single and double TILLING mutants that carry deleterious point mutations in these genes were isolated. RNAi-based gene-silencing plant lines, in which both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
349
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(361 citation statements)
references
References 47 publications
10
349
0
2
Order By: Relevance
“…A mapkkk knockout mutant of the Arabidopsis MAPKKK20 (MAP kinase kinase kinase) presents an improved salt tolerance, particularly in the later developmental stages (Gao and Xiang 2008). Additionally, the Arabidopsis double mutant mpk9/mpk12 loses water by transpiration less than the wild type (Jammes et al 2009). …”
Section: Map Kinase Complexity In Environmental Stresses' Signalingmentioning
confidence: 99%
“…A mapkkk knockout mutant of the Arabidopsis MAPKKK20 (MAP kinase kinase kinase) presents an improved salt tolerance, particularly in the later developmental stages (Gao and Xiang 2008). Additionally, the Arabidopsis double mutant mpk9/mpk12 loses water by transpiration less than the wild type (Jammes et al 2009). …”
Section: Map Kinase Complexity In Environmental Stresses' Signalingmentioning
confidence: 99%
“…The gain settings were selected to maximize the total Hoechst signal while preventing oversaturation. ethylene gas for 24 h were excised and submerged in an aqueous opening solution (5 mM KCl, 50 mM CaCl 2 , 10 mM MES buffer, pH 5.6) and incubated under cool-white light for 3 h. To induce stomatal closure, leaves were transferred to a similar opening solution with 20 mM ABA added to induce closure (Jammes et al, 2009). After incubation in the ABA solution under white light (100 mmol m 22 s 22 ) for 0, 45, 90, and 180 min, leaf peels were prepared and imaged using DIC imaging with a Zeiss Axio Observer D1 microscope with a Hamamatsu 1394 ORCA-ERA monochromatic camera (Jammes et al, 2009).…”
Section: Dcf and Hoechst Staining And Quantificationmentioning
confidence: 99%
“…ABI1 mediates signal transduction between ABA reception and ROS production under stress conditions (Murata et al 2001). The Previous studies indicated that MAP kinase signaling is activated following ROS accumulation, as testified to the induction of MPK3 and MPK6 by H 2 O 2 (Jammes et al 2009;Xing et al 2008). Interestingly, in this study, the expression of a B. napus homolog of MPK6 was significantly upregulated during drought stress.…”
Section: Stress Signaling Through Ros Regulationmentioning
confidence: 47%